Risk estimations, risk factors and genetic variants associated with Alzheimer Disease in selected publications from the Framingham Heart Study - Weinstein, Galit (2013)
The study of Alzheimer Disease (AD) in the Framingham Heart Study (FHS), a multi-generational, community-based population study, began nearly four decades ago. In this overview, we highlight findings from 7 prior publications that examined lifetime risk estimates for AD, environmental risk factors for AD, circulating and imaging markers of aging-related brain injury and explorations on the genetics underlying AD.